Barriers and facilitators influencing medication-related CDSS acceptance according to clinicians: A systematic review. (August 2021) - Westerbeek, Leonie; Ploegmakers, Kimberley J.; de Bruijn, Gert-Jan; Linn, Annemiek J.; van Weert, Julia C.M.; Daams, Joost G.; van der Velde, Nathalie; van Weert, Henk C.; Abu-Hanna, Ameen; Medlock, Stephanie
Highlights: This is the first summary of barriers and facilitators to medication-CDSS acceptance. We provide a systematic review of clinician-reported barriers and facilitators. These were mainly Technological factors (rather than Human or Organizational). Context was identified as an additional important factor. The findings can be used as a starting point for designing high-quality CDSSs. Abstract: Background: A medication-related Clinical Decision Support System (CDSS) is an application that analyzes patient data to provide assistance in medication-related care processes. Despite its potential to improve the clinical decision-making process, evidence shows that clinicians do not always use CDSSs in such a way that their potential can be fully realized. This systematic literature review provides an overview of frequently-reported barriers and facilitators for acceptance of medication-related CDSS. Materials and methods: Search terms and MeSH headings were developed in collaboration with a librarian, and database searches were conducted in Medline, Scopus, Embase and Web of Science Conference Proceedings. After screening 5404 records and 140 full papers, 63 articles were included in this review. Quality assessment was performed for all 63 included articles. The identified barriers and facilitators are categorized within the Human, Organization, Technology fit (HOT-fit) model. Results: A total of 327 barriers and 291 facilitators were identified. Results show that factors most often reported were related to (a lack of) usefulness and relevance of information, and ease of use and efficiency of the system. Discussion: This review provides a valuable insight into a broad range of barriers and facilitators for using a medication-related CDSS as perceived by clinicians. The results can be used as a stepping stone in future studies developing medication-related CDSSs.